2014
DOI: 10.2169/internalmedicine.53.2741
|View full text |Cite
|
Sign up to set email alerts
|

Phlegmonous Gastritis Associated with Group A Streptococcal Toxic Shock Syndrome

Abstract: Phlegmonous gastritis (PG) is a rare, acute, severe infectious disease of the gastric wall that is often fatal due to Streptococcus spp. A 77-year-old man with diabetes and a gastric ulcer was urgently admitted due to prolonged nausea and vomiting. Computed tomography revealed widespread diffuse thickening of the gastric wall, and PG was suspected. The patient expired less than 9 hours after admission despite intensive treatments. Later, an analysis of the blood and gastric juice revealed group A streptococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…EGD findings show an edematous mucosa with fibrinopurulent exudates and superficial ulcerations, loss of rugae, and poor distensibility; however, these features are nonspecific to PG. Several differential diagnoses need to be considered, like acute gastric mucosal lesion, scirrhous gastric cancer, gastric syphilis, corrosive gastritis, malignant lymphoma of the stomach, gastrointestinal stromal tumor, and anisakiasis[ 16 , 35 ]. Each of these diseases is diagnosed according to the collective findings from EGD imaging examination along with patient data on clinical pattern, medical history, and culture test results.…”
Section: Discussionmentioning
confidence: 99%
“…EGD findings show an edematous mucosa with fibrinopurulent exudates and superficial ulcerations, loss of rugae, and poor distensibility; however, these features are nonspecific to PG. Several differential diagnoses need to be considered, like acute gastric mucosal lesion, scirrhous gastric cancer, gastric syphilis, corrosive gastritis, malignant lymphoma of the stomach, gastrointestinal stromal tumor, and anisakiasis[ 16 , 35 ]. Each of these diseases is diagnosed according to the collective findings from EGD imaging examination along with patient data on clinical pattern, medical history, and culture test results.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical treatment is required in resistant or severe cases [ 12 ]. Given that fatal cases were occasionally reported, physicians need to make a correct diagnosis and start the appropriate treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the risk factors of PG: advanced age, infection, malnutrition, diabetes, immunosuppression, ulcer, achlorhydria, gastric mucosal injury from chronic gastritis, and gastric cancer. [ 6 , 8 , 23 ] Patients with hematological malignancies are commonly immunocompromized due to prolonged neutropenia, intensive chemotherapy, and the disease itself. Indeed, there are a few reports of PG occurring within days of immunosuppresant therapy.…”
Section: Discussionmentioning
confidence: 99%